+0  
 
+6
607
2
avatar

0,5*e^(X)-2 =2-e^X

 

ich komme nicht auf das Ergebnis :(

 29.11.2015

Beste Antwort 

 #2
avatar+25731 
+34

0,5*e^(X)-2 =2-e^X

 

Ich vermute die Gleichung heißt: \(0,5\cdot e^x-2 = 2-e^x\)

 

\(\small{ \begin{array}{rcll} 0,5\cdot e^x-2 &=& 2-e^x \qquad & | \qquad +2 \\ 0,5\cdot e^x &=& 4 \qquad & | \qquad +e^x \\ 0,5\cdot e^x +e^x &=& 4\\ 1,5\cdot e^x &=& 4 \qquad & | \qquad :1,5 \\ e^x &=& \frac{4}{1,5} \\ e^x &=& \frac{4\cdot 2}{3} \\ e^x &=& \frac{8}{3} \qquad & | \qquad \ln{()} \\ \ln{(e^x)} &=& \ln{( \frac{8}{3})} \\ x\cdot \ln{(e)} &=& \ln{( \frac{8}{3})} \qquad & | \qquad \ln{(e)} = 1 \\ x &=& \ln{( \frac{8}{3})} \\ x &=& \ln{(8)} - \ln{(3)} \\ x &=& 2,07944154168 - 1,09861228867 \\ x &=& 0,98082925301 \\ \end{array} }\)

laugh

 30.11.2015
 #1
avatar
0

Ich komme auf:

 

e^x + e^x = 8 

 

aber das ist falsch.

 29.11.2015
 #2
avatar+25731 
+34
Beste Antwort

0,5*e^(X)-2 =2-e^X

 

Ich vermute die Gleichung heißt: \(0,5\cdot e^x-2 = 2-e^x\)

 

\(\small{ \begin{array}{rcll} 0,5\cdot e^x-2 &=& 2-e^x \qquad & | \qquad +2 \\ 0,5\cdot e^x &=& 4 \qquad & | \qquad +e^x \\ 0,5\cdot e^x +e^x &=& 4\\ 1,5\cdot e^x &=& 4 \qquad & | \qquad :1,5 \\ e^x &=& \frac{4}{1,5} \\ e^x &=& \frac{4\cdot 2}{3} \\ e^x &=& \frac{8}{3} \qquad & | \qquad \ln{()} \\ \ln{(e^x)} &=& \ln{( \frac{8}{3})} \\ x\cdot \ln{(e)} &=& \ln{( \frac{8}{3})} \qquad & | \qquad \ln{(e)} = 1 \\ x &=& \ln{( \frac{8}{3})} \\ x &=& \ln{(8)} - \ln{(3)} \\ x &=& 2,07944154168 - 1,09861228867 \\ x &=& 0,98082925301 \\ \end{array} }\)

laugh

heureka 30.11.2015

65 Benutzer online

avatar
avatar
avatar
avatar